Characterizing Nosocomial Bacterial Pathogens and Antibiotic Resistance at a Major Referral Hospital in Western Kenya - Aroko, Arthur; Onguru, Daniel; Ibrahim, Daud (International Journal of Public Health and Epidemiology Research, 2023)
Bacterial pathogens responsible for hospital acquired infections in Jaramogi Oginga Odinga Teaching and Referral Hospital are difficult to treat due to their tendency to resist most antibiotics used against them. This study aimed at characterizing bacterial pathogens associated with hospital acquired infections from clinical specimens and determining their antibiotic resistance. A descriptive cross-sectional study design involving bacteriological analysis of clinical samples was used to purposively select 111 patients who exhibited signs and symptoms of hospital acquired infections from whom, samples were obtained and analyzed. Tables, pie charts and bar graphs were used to summarize data. Prevalence was determined using percentages while the relationship between patient characteristics and the risk of contracting nosocomial bacteria was determined using Chisquare. P values ≤ 0.05 were considered statistically significant. Of the 111 samples obtained 59 (53.2%) were from females. About one-third (31%) were younger than one year while 4% were aged between 6 and 12 years. A total of 51(45.9%) of the samples yielded bacterial growth. There was an association between age and the risk of infection (p=0.012). Sex was not associated with the risk of infection (p=0.338). Most pathogens (n=27,52.9%) were isolated from surgical patients. Gram negative bacteria (n=37, 33.6%) were more prevalent with Klebsiella spp., being frequently isolated. The isolated pathotypes were not significantly associated with patient category (p=0.774). Ampicillin, imipenem and ceftazidime showed (100%, n=17), (97.1%, n=33) and (92.1%, n=35) resistance respectively. Amikacin, Gentamycin and Meropenem showed (7.3%, n=3), (22.2%, N=8) and (24.1%, N=7) resistance respectively. A high prevalence antimicrobial resistance was detected. Klebsiella spp., was the most common pathotype causing nosocomial infection. We recommend continued surveillance to detect increasing resistance on Amikacin, Gentamycin and Meropenem due to empiric use as well as antimicrobial stewardship to fight threats that may emerge.
Keywords: Antimicrobial; Resistance; Nosocomial; Surgical; JOOTRH